2017
DOI: 10.1016/j.ypmed.2016.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Principles and strategies for improving the prevention of cardio-metabolic diseases in indigenous populations: An international Delphi study

Abstract: The disparity in life expectancy between Indigenous and non-Indigenous populations is being driven by a heightened incidence of cardio-metabolic diseases, and is at least partly underpinned by educational, economic and historical determinants. However, there is a lack of consensus with regards to priorities for tackling these determinants. Therefore, the current study recruited experts in Indigenous cardio-metabolic health from Australia, New Zealand and the United States, in order to establish local consensus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In this study, we identified both behavioural (e.g., smoking) and biological (e.g., diabetes and sleep‐disordered breathing) determinants of poor sleep, potentially indicating that simple sleep health education, particularly surrounding sleep habits and consequences of sleep problems, may be beneficial for improvement of sleep. However, when considering such programmes, the complex combination and the ongoing impact of historical, institutional, sociocultural, economic, environmental and lifestyle‐related factors, as well as access to healthcare, must be remembered in Indigenous people (Stoner et al., 2017). Of utmost importance, if any sleep health education programme is to be developed and implemented in Indigenous populations, it is imperative that these programmes are developed in consultation with, informed and identified by, the Indigenous community.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified both behavioural (e.g., smoking) and biological (e.g., diabetes and sleep‐disordered breathing) determinants of poor sleep, potentially indicating that simple sleep health education, particularly surrounding sleep habits and consequences of sleep problems, may be beneficial for improvement of sleep. However, when considering such programmes, the complex combination and the ongoing impact of historical, institutional, sociocultural, economic, environmental and lifestyle‐related factors, as well as access to healthcare, must be remembered in Indigenous people (Stoner et al., 2017). Of utmost importance, if any sleep health education programme is to be developed and implemented in Indigenous populations, it is imperative that these programmes are developed in consultation with, informed and identified by, the Indigenous community.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, most commonly injured are articular ligaments, intramuscular tendons, tendon attachments. When applying loads only to the force direction, the process of adaptation by the cardiovascular and respiratory systems (Stoner, Matheson, Perry, Williams, McManus, Holdaway, ... Maiorana, 2017;van der Ster, Bennis, Delhaas, Westerhof, Stok, & van Lieshout, 2018). But these are the main systems for ensuring the normal level of human life.…”
Section: Discussionmentioning
confidence: 99%
“…An option that received a rank of ‘1’ was most important. To derive aggregated scores across each expert group, each rank was awarded a score: rank 1 = 3 points, rank 2 = 2 points and rank 3 = 1 point (Stoner et al, 2017 ). This method of calculation awarded highest points to the option ranked first and the lowest point to the option ranked third by each panel member.…”
Section: Methodsmentioning
confidence: 99%